Transanal total mesorectal excision for abdominoperineal resection is associated with poor oncological outcomes in rectal cancer patients: A word of caution from a multicentric Canadian cohort study. (10th January 2022) - Caycedo‐Marulanda, Antonio; Verschoor, Chris P.; Brown, Carl P.; Karimuddin, Ahmer; Raval, Manoj; Phang, Terry; Vikis, Elena; Melich, George; Patel, Sunil V.; ,
Abstract: Aim: The main objective of this study was to compare the oncological outcomes of patients undergoing abdominoperineal resection (APR) versus low anterior resection (LAR) through a transanal total mesorectal excision (taTME) approach. Method: A total of 360 adult patients with a diagnosis of rectal cancer were enrolled at participating centres from the Canadian taTME Expert Collaboration. Forty‐three patients received taTME‐APR and received 317 taTME‐LAR. Demographic, operative, pathological and follow‐up data were collected and merged into a single database. Results are presented as hazard ratio (HR) and 95% confidence interval. All analyses were performed in the R environment (v.3.6). Results: The proportion of patients with a positive circumferential radial margin status was higher in the taTME‐APR group than the taTME‐LAR group (21% vs. 9%, p = 0.001). Complete TME was achieved in 91% of those undergoing APR compared with 96% of those undergoing LAR ( p = 0.25). APR was associated with a greater rate of local recurrence relative to LAR, although it was not significant [crude HR = 3.53 (95% CI 0.92–13.53)]. Circumferential margin positivity was significantly associated with a higher rate of systemic recurrence [crude HR = 3.59 (95% CI 1.38–9.3)]. Conclusion: Our results demonstrate inferior outcomes in those undergoing taTME‐APR compared with taTME‐LAR. The use of this technique for this particular indication needs to be carefully considered.